2020
DOI: 10.1186/s13071-020-04156-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing a national atlas to support the progressive control of tsetse-transmitted animal trypanosomosis in Kenya

Abstract: Background: African animal trypanosomosis (AAT) is a major livestock disease in Kenya. Even though, over the years various organizations have collected a vast amount of field data on tsetse and AAT in different parts of the country, recent national-level maps are lacking. To address this gap, a national atlas of tsetse and AAT distribution is being developed by the Kenya Tsetse and Trypanosomosis Eradication Council (KENTTEC) and partners. Methods: All data collected by KENTTEC from 2006 to 2019 were systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…swynnertoni was less abundant. This finding corroborates previous studies in which these two savannah tsetse species were found to be predominant in the Maasai Mara-Serengeti ecosystem of Kenya and Tanzania [ 5 , 53 ]. As both species are competent vectors of human and animal trypanosomes [ 52 , 54 , 55 ], their presence highlights the persistent risk of AAT and HAT in the MMNR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…swynnertoni was less abundant. This finding corroborates previous studies in which these two savannah tsetse species were found to be predominant in the Maasai Mara-Serengeti ecosystem of Kenya and Tanzania [ 5 , 53 ]. As both species are competent vectors of human and animal trypanosomes [ 52 , 54 , 55 ], their presence highlights the persistent risk of AAT and HAT in the MMNR.…”
Section: Discussionsupporting
confidence: 92%
“…African trypanosomiasis is endemic in regions inhabited by the insect vector in 37 countries in Africa, rendering approximately 70 million people and 60 million cattle in AT-endemic regions are at risk of infection [1,2]. Consequently, reduced productivity due to chronic disease in humans and animals and loss of livestock through death threatens food security, quality of living, and economic stability, particularly in regions where pastoralism is the main economic activity [3][4][5]. Therefore, more effective AT control and management strategies are required.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of assembling, harmonizing and geo-referencing tsetse and AAT data collected by the TCD and DVFS for the period 2000-2019 has been achieved. This national atlas for Zimbabwe follows the ones for Sudan [12], Mali [22] and Kenya [23], but vastly exceeds them in terms of the number of data points. In particular, the overall trapping effort in Zimbabwe is approximately 1 million trap days, compared to < 20,000 trap days in other countries.…”
Section: Discussionmentioning
confidence: 82%
“…However, a unified, centralized and regularly updated database was never developed, thus hampering evidence-based decisionmaking. Against this backdrop, the FAO continental atlas of tsetse and AAT [13,20,21] provided the blueprint to develop a national atlas in Zimbabwe and in other countries [12,22,23]. The development of national atlases was also spurred by the need to inform the progressive control pathway (PCP) for AAT [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tsetse habitat in the eastern region of Rwanda has reduced greatly due to the demographic pressure. The remaining savannah habitat seems to favour G. pallidipes, which tends to dominate other savannah species in the region (Ciosi, Masiga, and Turner 2014; Saarman et al 2019) ; [52]. The high tsetse abundance in Akagera NP was found all year round with seasonal variations from wet to dry season.…”
Section: Discussionmentioning
confidence: 94%